Analisis Dugaan Kerusakan Rumah Yang Berdekatan Dengan Menara Telekomunikasi - Suhendra, Suhendra; Yusiana, Venny (Journal of Electrical Power Control and Automation (JEPCA), 2023)
In general lightning will predominantly strike parts of the earth's surface that have tall structures (tall buildings, BTS towers, high voltage transmission towers) and prefer structures made of conductive materials such as metal. The existence of a house close to a Telecommunication Tower is the background for this research. The research aims to analyze suspected damage that occurred to residential buildings that are very close to telecommunications tower activity. The method used is a general study of the feasibility of telecommunications towers as well as the types and patterns of damage that occurred in the houses studied. The results show that the damage that occurs to houses is mostly caused by the bearing capacity of the soil which is less affected by the shrinkage of the concrete. A comprehensive assessment needs to be carried out for telecommunications towers, especially the lightning conduction and grounding systems.